NATURAL CONVECTION HEAT TRANSFER IN A VERTICAL CONCENTRIC ANNULUS (Journal of Engineering, 2007)
Experiments were carried out to study the local and average heat transfer by natural convection ina vertical concentric cylindrical annulus. The experimental setup consists of an annulus has a radius ratio of 0.555 and inner cylinder with a heated length 1.2m subjected to the constant heat flux while the outer cylinder is subjected to the ambient temperature. The investigation covers heat flux range from 58.2 W/m2 to 274.31 W/m2. Results show an increase in the natural convection as heat flux increases leads to an improve in the heat transfer process. An empirical equation of average Nusselt number as a function of Raylieh number was deduced